A novel spiral channel with the growing waviness on the sidewalls for compact high-efficiency heat exchanger. (1st October 2021) - Zhang, L.Y.; Cui, X.; Lu, Z.; Miao, C.Y.; Jin, L.W.
Highlights: A novel spiral channel characterized by wavy sidewalls is proposed. The proposed spiral-wavy channel exhibits a superior heat transfer performance. Heat transfer in the spiral-wavy channel is enhanced along the flow direction. Quasi boundary layers are defined to reveal the heat transfer process. Abstract: Spiral channels are widely used as the core heat exchangers in latent thermal storage units. This study aims to develop a novel spiral channel characterized by wavy sidewalls for high-efficiency convective heat transfer in tube side. The amplitude of the wavy sidewalls is designed to grow from the inlet to the outlet along flow direction. The thermal characteristics in the spiral-wavy channel were numerically investigated under the boundary condition of constant wall temperature, since latent heat storage units mainly work under isothermal condition. The comparison was carried out between a smooth-spiral channel and a spiral-wavy channel in terms of the heat transfer capacity, friction factor, dimensionless temperature distributions and development of boundary layers. At a given heat transfer rate, the required length of the spiral-wavy channel is only 63.5% of that of the smooth-spiral channel, which implies that the energy density and efficiency of a heat storage unit can be improved remarkably. The increase in pressure drop brought by the spiral-wave channel is less important compared with the improvement of thermal performance, suggesting its potential in heat transfer enhancement and energy saving. The present work is expected to motivate the design of compact and high-efficiency heat exchangers for thermal energy storage and extraction.